Susceptibility of Pseudomonas aeruginosa Recovered from Cystic Fibrosis Patients to Murepavadin and 13 Comparator Antibiotics - Ekkelenkamp, Miquel B. (Antimicrob Agents Chemother, 2020)
The objective was to determine the in vitro antimicrobial susceptibility of Pseudomonas aeruginosa isolates cultured from cystic fibrosis (CF) patients and explore associations between strain sequence type and susceptibility. Fourteen antibiotics and antibiotic combinations, including the novel antibacterial peptide murepavadin, were tested for activity against 414 Pseudomonas aeruginosa isolates cultured from respiratory samples of CF patients. The complete genomes of the isolates were sequenced, and minimum spanning trees were constructed based on the sequence types (STs). Percentages of resistance according to CLSI 2019 breakpoints were as follows: cefepime, 14%; ceftazidime, 11%; ceftazidime-avibactam, 7%; ceftolozane-tazobactam, 3%; piperacillin-tazobactam, 12%; meropenem, 18%; imipenem, 32%; aztreonam, 23%; ciprofloxacin, 30%; gentamicin, 30%; tobramycin, 12%; amikacin, 18%; and colistin, 4%. Murepavadin MIC(50) and MIC(90) were 0.12 mg/liter and 2 mg/liter, respectively. There were no apparent clonal clusters associated with resistance, but higher MICs did appear to occur more often in STs with multiple isolates than in single ST isolates. In general, the CF isolates showed a wide genetic distribution. P. aeruginosa CF isolates exhibited the lowest resistance rates against ceftolozane-tazobactam, ceftazidime-avibactam, and colistin. Murepavadin demonstrated the highest activity on a per-weight basis and may therefore become a valuable addition to the currently available antibiotics for treatment of respiratory infection in people with CF.